2021
DOI: 10.3390/genes12121850
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Environment Interactions in Schizophrenia: A Literature Review

Abstract: Schizophrenia is a devastating mental illness with a strong genetic component that is the subject of extensive research. Despite the high heritability, it is well recognized that non-genetic factors such as certain infections, cannabis use, psychosocial stress, childhood adversity, urban environment, and immigrant status also play a role. Whenever genetic and non-genetic factors co-exist, interaction between the two is likely. This means that certain exposures would only be of consequence given a specific gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 106 publications
0
47
0
2
Order By: Relevance
“…COMT might, however, confer a small risk for schizophrenia that is difficult to detect or it may not directly act on the risk for the disease, but modulate the impact of other risk factors such as environmental ones. In fact, despite the high heritability of schizophrenia, it is well-recognized that genetic factors not only coexist with nongenetic risk factors, but also interact with them [ 9 ]. Thus, the influence of COMT Val105/158Met on behaviour may be better understood in terms of gene–environment interactions, as both type of factors seem to converge on common networks implicated in brain function [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COMT might, however, confer a small risk for schizophrenia that is difficult to detect or it may not directly act on the risk for the disease, but modulate the impact of other risk factors such as environmental ones. In fact, despite the high heritability of schizophrenia, it is well-recognized that genetic factors not only coexist with nongenetic risk factors, but also interact with them [ 9 ]. Thus, the influence of COMT Val105/158Met on behaviour may be better understood in terms of gene–environment interactions, as both type of factors seem to converge on common networks implicated in brain function [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high heritability of schizophrenia, it is well-recognized that nongenetic factors such as certain neurotropic infections and other early life stressors can also play a role [ 6 , 7 , 8 , 9 ]. Maternal exposure to the influenza virus during pregnancy could increase the risk for schizophrenia in offspring, and other neurotropic viruses have been assessed as infectious agents increasing the risk for schizophrenia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SCZ is related with an approximately 15-year reduction in life expectancy in comparison to the gross population and a 5-10 percent lifetime risk of suicide. The low quality of life caused by cognitive impairment and mortality risks make SCZ a severe public health burden (Cloutier et al, 2016;Avramopoulos, 2018;Wahbeh and Avramopoulos, 2021). Despite the abundance of literature of SCZ manifestations, its exact etiology and pathogenesis are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence have shown that relatives of patients with schizophrenia have a 5–10 times higher risk of developing schizophrenia ( 3 ), and those with a positive family history of mental illness are more likely to develop the problem at a younger age ( 4 ). Moreover, many environmental factors have been identified to contribute to the risk of developing schizophrenia at various times, especially during development stages (prenatal life, perinatal life, adolescence, and adulthood) ( 5 ). Such environmental factors have additive or cumulative effects, which may be linked and/or share causal factors ( 6 ).…”
Section: Introductionmentioning
confidence: 99%